2012
DOI: 10.1371/journal.pone.0047457
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Transcription Factor GTF2IRD2 in Executive Function in Williams-Beuren Syndrome

Abstract: Executive functions are amongst the most heritable cognitive traits with twin studies indicating a strong genetic origin. However genes associated with this domain are unknown. Our research into the neurodevelopmental disorder Williams-Beuren syndrome (WBS) has identified a gene within the causative recurrent 1.5/1.6 Mb heterozygous microdeletion on chromosome 7q11.23, which may be involved in executive functioning. Comparative genome array screening of 55 WBS patients revealed a larger ∼1.8 Mb microdeletion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 60 publications
(62 reference statements)
3
25
0
1
Order By: Relevance
“…Initially, the examination of visuospatial performance by HR and JB seems indicative of the additive effect of deleting each of the GTF2I family genes on the severity of cognitive impairment, and is in line with other findings in individuals with extended deletions (approximately 1.8 Mb) that encompass GTF2IRD2 , who present with significantly greater neurological impairments than individuals with shorter deletions typical of WS [59]. However, although we cannot dismiss the effects of other deleted genes in JB that extend beyond the WSCR on cognitive functioning, JB’s high level of performance on small-scale mental rotation and VPT rules out the conclusion of a general deficit, and excludes the role of genes telomeric to GTF2I in these specific small-scale spatial abilities.…”
Section: Discussionsupporting
confidence: 79%
“…Initially, the examination of visuospatial performance by HR and JB seems indicative of the additive effect of deleting each of the GTF2I family genes on the severity of cognitive impairment, and is in line with other findings in individuals with extended deletions (approximately 1.8 Mb) that encompass GTF2IRD2 , who present with significantly greater neurological impairments than individuals with shorter deletions typical of WS [59]. However, although we cannot dismiss the effects of other deleted genes in JB that extend beyond the WSCR on cognitive functioning, JB’s high level of performance on small-scale mental rotation and VPT rules out the conclusion of a general deficit, and excludes the role of genes telomeric to GTF2I in these specific small-scale spatial abilities.…”
Section: Discussionsupporting
confidence: 79%
“…Compared to WBS patients with a typical 1.5-Mb deletion, only 2 additional genes, NCF1 and GTF2IRD2 , are deleted in those with a larger 1.8-Mb size deletion. After analyzing cognitive, behavioral and psychological functioning in 55 WBS patients, Porter et al [2012] showed that those with 1.8-Mb deletions encompassing GTF2IRD2 had significantly poorer cognitive functions including spatial functioning, social reasoning, and executive function. The GTF2IRD1 and GTF2I are the transcription factor TFII-I family members encoding BEN and TFII-I proteins, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria included the presence of uncorrected hearing or vision impairment and the presence of major medical problems. All participants with WS had their diagnosis confirmed with the positive fluorescent in situ hybridization (FISH) test and displayed the typical ~1.6 Mb heterozygous microdeletion at 7q11.23 [51]. …”
Section: Methodsmentioning
confidence: 99%